Policy Impact Analysis of The Harapan Family Program to Improve a Poor Household Welfare in Pardomuan Village Onanrunggu District Samosir Regency - Dodi Pramana; Nelly Armayanti; Rita Dialusi Gultom (Department of Public Administration, 2022)
Poverty is a condition of a person or group whose basic rights are not fulfilled to maintain and develop a dignified life.The government overcomes poverty through various efforts, one of which is the Family Hope Program (PKH). This program aims to improve the community's welfare and overcome long-term problems, especially for those with Very Poor Households (RTSM). The Family Hope Program (PKH) has been implemented in Pardomuan Village, Onanrunggu District, Samosir Regency because many people are classified as Very Poor Households (RTSM). This research method uses a qualitative approach with a descriptive analysis research type. The study results obtained statements related to the socio-economic conditions of PKH recipients and the efficiency of PKH in overcoming poverty. The Family Hope Program (PKH) has been proven to be able to improve the welfare of people with Very Poor Households (RTSM) in Pardomuan village, especially by helping to meet the educational needs of children, supporting the health of pregnant women and toddlers, and meeting the needs of the elderly over 70 years old or with severe disabilities. Therefore, it can be concluded that the implementation of PKH can alleviate poverty, especially in RTSM in Pardomuan Village, Onanrunggu District, Samosir Regency, and can bring prosperity to the community.